Becoming Human with Humanoid From Physical Interaction to Social Intelligence - Hoirul Basori, Ahmad; Leylavi Shoushtari, Ali; Venelinov Topalov, Andon (IntechOpen, 2020)
Nowadays, our expectations of robots have been significantly increases. The robot, which was initially only doing simple jobs, is now expected to be smarter and more dynamic. People want a robot that resembles a human (humanoid) has and has emotional intelligence that can perform action-reaction interactions. This book consists of two sections. The first section focuses on emotional intelligence, while the second section discusses the control of robotics. The contents of the book reveal the outcomes of research conducted by scholars in robotics fields to accommodate needs of society and industry.